No One Can Know - Marshall, Kate Alice (New York : Flatiron Books, 2024)
"The author of What Lies in the Woods returns with a novel about three sisters, two murders, and too many secrets to count. Emma hasn't told her husband much about her past. He knows her parents are dead and she hasn't spoken to her sisters in years. Thenthey lose their apartment, her husband gets laid off, and Emma discovers she's pregnant-right as the bank account slips into the red. That's when Emma confesses that she has one more asset: her parents' house, which she owns jointly with her estranged sisters. They can't sell it, but they can live in it. But returning home means that Emma is forced to reveal her secrets to her husband: that the house is not a run-down farmhouse but a stately mansion, and that her parents died there. Were murdered. And that some people say Emma did it. Emma and her sisters have never spoken about what really happened that night. Now, her return to the house may lure her sisters back, but it will also crack open family and small-town secrets lots of people don't want revealed. As Emma struggles to reconnect with her old family and hold together her new one, she begins to realize that the things they have left unspoken all these years have put them in danger again"--.
new book 2024 winter.
Keywords: Women Sleuths; Suspense fiction; Thrillers; Mystery & Detective; Novels